Development of an Inquiry-Based Science Module on Plant Parts and Their Functions in Elementary Schools - Maymunah, Ana; Ramorola, Mmankoko; Shobowale, Ishola Olukayode (Journal of Educational Technology and Learning Creativity, 2023)
Purpose of the study: The aim of this research is to produce a product in the form of an inquiry-based science module for class IV elementary school and to determine students' responses to the feasibility of an inquiry-based science module on plant parts and their functions. Methodology: This type of research uses the R & D (Research and Development) development method. The data collection technique in this research is using observation sheets, interview sheets, and questionnaires. Data analysis uses descriptive statistics. Qualitative data will be analyzed logically and meaningfully, while quantitative data will be analyzed using average calculations. Main Findings: The main result of this research is that a module is obtained that is suitable for use as teaching material in class IV elementary schools on science learning material regarding plants and their functions. This is demonstrated based on the assessment of material experts, media experts and teachers with the ideality of the material being explained in detail accompanied by illustrations or picture descriptions, the material is also explained using an inquiry approach, and the module contains information that increases students' knowledge. This is confirmed by the average assessment percentage of 87.9% for material experts, 84.1% for media experts, and 84.9% for teachers. Novelty/Originality of this study: Then the novelty of this research lies not only in conveying knowledge about plant parts and their functions but also in fostering a deep curiosity and appreciation of nature through an interactive, inquiry-based learning approach.